Counteractive effects of predator invasion and habitat destruction on predator–prey systems - Jing Zhang; Linying Wang; Yinghui Yang; Haoqi Liu (Ecology and Evolution, 2024)
Abstract Alien species invasion and habitat destruction are among the primary threats to native animal communities, particularly for native predator–prey systems. However, when predator invasion and habitat destruction co‐occur, it remains unclear whether their respective threats to native systems compensate each other or accumulate, as well as how these effects respond to the different characteristics of predator invasion and habitat destruction. In this study, we developed a spatially explicit simulation model with one prey species and one predator species and exposed it to invasive predators and habitat destruction with different properties. The results revealed the following insights: (1) Habitat destruction can compensate threats to native predator–prey systems from global predator invasion only when native predators possess predation capability similar to those of the invaders. In other scenarios, cumulative effects arise from predator invasion and habitat destruction. (2) Low levels of habitat destruction occurring at a faster rate, in conjunction with a substantial number of global invasive predators being present, can better compensate their respective threats to native predator–prey systems than the other scenarios. These findings provide valuable insights into situations where habitat destruction and alien species invasion coincide. They raise the question of whether we can leverage the interaction between them to reduce threats to biodiversity.